2000
DOI: 10.1542/peds.106.2.e16
|View full text |Cite
|
Sign up to set email alerts
|

The Value of First-Day Bilirubin Measurement in Predicting the Development of Significant Hyperbilirubinemia in Healthy Term Newborns

Abstract: A serum bilirubin measurement and the use of the critical bilirubin level of 6 mg/dL in the first 24 hours of life will predict nearly all of the term newborns who will have significant hyperbilirubinemia and will determine all those who will require a phototherapy treatment later during the first days of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 20 publications
5
73
1
5
Order By: Relevance
“…Thus all new borns should be considered for screening irrespec ve of sex and mode of delivery. This was consistent with observa ons of S Umit et al 12,17 and Frauk Aplay et al 4 Birth weight did not have any bearing on the development of signifi cant jaundice. Mean birth wt.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus all new borns should be considered for screening irrespec ve of sex and mode of delivery. This was consistent with observa ons of S Umit et al 12,17 and Frauk Aplay et al 4 Birth weight did not have any bearing on the development of signifi cant jaundice. Mean birth wt.…”
Section: Discussionsupporting
confidence: 91%
“…Frauk Aplay et al reported 3310±305gm Vs 3240±34gm in hyperbilirubinaemia and non hyprebilirubinaemia group respec vely. 4 S Umit Sarici et al reported birth weight of 2794±418gm and 2772±157gm in two groups. 17 S Umit et al observed mean birth weight of 3214±828gmgm and 3212± 196 gm in two groups 12 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many investigators have tried to find a simple marker to predict hyperbilirubinemia and its subsequent course in newborns like cord bilirubin estimation 12,13 , bilirubin estimation during 6 to 24 hours of age [14][15][16][17] , predischarge hour specific bilirubin estimation 18 and transcutaneous bilirubin measurement [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Alpay ve ark. [21] da hemoglobin düzeyi, cins, doğum şekli, doğum tartısı, gestasyonel yaş ve maternal sigara içimi gibi faktörler-le hiperbilirubinemi arasında anlamlı bir ilişki saptamamışlardır.…”
Section: Discussionunclassified